Alternative splicing in shaping the molecular landscape of the cochlea - Kim, Kwan Soo; Koo, Hei Yeun; Bok, Jinwoong (Frontiers in Cell and Developmental Biology, 2023)
The cochlea is a complex organ comprising diverse cell types with highly specialized morphology and function. Until now, the molecular underpinnings of its specializations have mostly been studied from a transcriptional perspective, but accumulating evidence points to post-transcriptional regulation as a major source of molecular diversity. Alternative splicing is one of the most prevalent and well-characterized post-transcriptional regulatory mechanisms. Many molecules important for hearing, such as cadherin 23 or harmonin, undergo alternative splicing to produce functionally distinct isoforms. Some isoforms are expressed specifically in the cochlea, while some show differential expression across the various cochlear cell types and anatomical regions. Clinical phenotypes that arise from mutations affecting specific splice variants testify to the functional relevance of these isoforms. All these clues point to an essential role for alternative splicing in shaping the unique molecular landscape of the cochlea. Although the regulatory mechanisms controlling alternative splicing in the cochlea are poorly characterized, there are animal models with defective splicing regulators that demonstrate the importance of RNA-binding proteins in maintaining cochlear function and cell survival. Recent technological breakthroughs offer exciting prospects for overcoming some of the long-standing hurdles that have complicated the analysis of alternative splicing in the cochlea. Efforts toward this end will help clarify how the remarkable diversity of the cochlear transcriptome is both established and maintained.